Self-assembly of conjugated units using metal-terpyridine coordination - Gao, Yang (2014)
Due to their inherently dynamic natures and fascinating photoluminescent/photoelectronic properties, coordination compounds of metal ions and conjugated terpyridine ligands have attracted considerable attention as functional materials for a variety of potential applications. In this feature article, a summary of recent work toward the development of one- (1D), two- (2D), and three-dimensional (3D) supramolecular polymers, networks, and metallomacrocycles based on zinc metal ion coordination of conjugated units bearing terpyridine ligands is presented, and it is shown how it fits within the overall framework of work in this field. Here, a sequential study from terpyridines as basic building blocks to their zinc-coordinated supramolecular 1D polymers, 2D macrocycles, and 2D and 3D networks is developed. These networks are compared with respect to their thermal stabilities, molecular organization, and linear and nonlinear optical properties. This work opens new prospects for the development of supramolecular chemistry of terpyridines and other transition metal ions, and also their application in future optoelectronic devices.